Urban Economy Development and Ecological Carrying Capacity: Taking Beijing City as the Case. (May 2017) - Fang, Wei; An, Haizhong; Li, Huajiao; Gao, Xiangyun; Sun, Xiaoqi
Abstract: A city can obtain most of natural resources from outside of city for its development, but the ecological carrying capacity of it is limited. Urban economic development in some countries or areas is still maintained a high speed, but their ecological environment has deteriorated sharply. That means their economic has grown out of the limit of ecological carrying capacity. In the paper, the urban ecosystem is divided into population subsystem, economy subsystem, and resources and environment subsystem; the relationship among the three subsystems is analyzed based on eco-economic theories; after then, a theoretical framework of urban ecological carrying capacity is established. Due to urban ecosystem is a dynamic system with complex feedbacks, a System Dynamics model including three subsystems for is set up to measure urban ecological carrying capacity. Finally, the relationship between ecological carrying capacity and economic development in Beijing city from 1996 to 2012 were analyzed. Three scenarios in different economic growth pace are designed; the tendencies of deterioration of ecological environment in Beijing under different Scenarios are analyzed to explore the balance between economic development and ecological protection.